2009
DOI: 10.1007/s00420-009-0455-0
|View full text |Cite
|
Sign up to set email alerts
|

French cohort of the uranium processing workers: mortality pattern after 30-year follow-up

Abstract: In spite of limited statistical power, results show consistency with previous studies of nuclear workers potentially exposed to uranium. Further investigation based on more precise uranium exposure data should allow the estimation of uranium hazard effects among this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…this finding is likely due to the known healthy worker effect in occupational cohorts and consistent with the results from many other uranium worker studies (Pinkerton et al 2004;Boice et al 2008;ritz 1999;Silver et al 2013;Dupree-Ellis et al 2000;guseva canu et al 2010). no statistically significant excesses in any of the subgroups of causes of deaths, including lung cancer and stomach cancer, have been found in the present study, which is again in line with the findings of other studies.…”
Section: Discussionsupporting
confidence: 95%
“…this finding is likely due to the known healthy worker effect in occupational cohorts and consistent with the results from many other uranium worker studies (Pinkerton et al 2004;Boice et al 2008;ritz 1999;Silver et al 2013;Dupree-Ellis et al 2000;guseva canu et al 2010). no statistically significant excesses in any of the subgroups of causes of deaths, including lung cancer and stomach cancer, have been found in the present study, which is again in line with the findings of other studies.…”
Section: Discussionsupporting
confidence: 95%
“…It included 2709 male workers employed at the plant for at least 6 months between 1960 and 2005, who had never been uranium miners. The mortality pattern and association between internal uranium exposure and cancer mortality in this cohort had been studied and reported previously 10 11…”
Section: Introductionmentioning
confidence: 78%
“…Potential confounding problems were addressed by stratification of each model on sex and 10-year birth cohort and by adjustment on, four-class SES at hire in order to account for differential baseline risk across the SES categories 10. Furthermore, each model was adjusted on exposure to heat, aromatic solvents (eg, solvents containing aromatic hydrocarbons, such as benzene, toluene, xylene or styrene), TCE and shift-work, which were considered as time-dependent covariates in models, without lag.…”
Section: Methodsmentioning
confidence: 99%
“…Large pooled studies of nuclear reactor workers showed significantly increased risks of solid cancers and leukemia, (Cardis et al 2007 ; Gillies and Haylock 2014 ; Muirhead et al 2009 ; Richardson et al 2015 ; Schubauer-Berigan et al 2015 ) and, more recently and controversially, of cardiovascular (CVD) (Azizova et al 2015 ; Muirhead et al 2009 ) and non-malignant respiratory diseases (Azizova et al 2017 ; Muirhead et al 2009 ). Only a few studies have examined risks of exposures in the uranium processing industry (Boice et al 2008 ; Dupree-Ellis et al 2000 ; Dupree et al 1987 ; Guseva Canu et al 2010 ; Kreuzer et al 2015 ; Nusinovici et al 2010 ; Pinkerton et al 2004 ; Richardson et al 2013 ; Silver et al 2013 ; Zablotska et al 2013 ) and reported contradictory results, necessitating further research in this area. In comparison to the general population, uranium processing workers had higher mortality rates from lung cancer (Pinkerton et al 2004 ; Silver et al 2013 ; Zablotska et al 2013 ), lymphatic and hematopoietic, particularly non-Hodgkin lymphoma (NHL) and multiple myeloma (MM), cancers (Guseva Canu et al 2010 ; Kreuzer et al 2015 ; Pinkerton et al 2004 ; Richardson et al 2013 ; Silver et al 2013 ), and kidney or bladder cancers (Boice et al 2008 ; Dupree-Ellis et al 2000 ; Kreuzer et al 2015 ; Richardson et al 2013 ; Zablotska et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%